2006
DOI: 10.1002/ch.316
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted approach to the treatment of phantom limb pain using hypnosis

Abstract: This study looks at the efficacy of a multifaceted approach to the relief of phantom limb pain. Using hypnosis, four therapeutic interventions are incorporated into this treatment: hypnotic analgesia; visualization and movement of an imaginary limb to facilitate the movement of the phantom limb; psychological therapy and self-hypnosis. Twenty-five amputees completed a course of hypnosis averaging six weekly sessions. All patients were taught self-hypnosis and encouraged to continue this practice on a daily bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
(8 reference statements)
0
5
0
2
Order By: Relevance
“…Reports of cases indicate substantial improvement in PLP with hypnosis training Table 2). 30,38,40 In the small clinical trial, patients 6 mos postamputation with PLP were randomized to either three individual sessions of hypnosis for PLP or the waitlisted control group. Repeated-measures analysis of variance showed statistically significant time-by-group effects ( P < 0.001) in the McGill Pain Questionnaire Pain Intensity Rating and the Daily Pain Rating Scale.…”
Section: Resultsmentioning
confidence: 99%
“…Reports of cases indicate substantial improvement in PLP with hypnosis training Table 2). 30,38,40 In the small clinical trial, patients 6 mos postamputation with PLP were randomized to either three individual sessions of hypnosis for PLP or the waitlisted control group. Repeated-measures analysis of variance showed statistically significant time-by-group effects ( P < 0.001) in the McGill Pain Questionnaire Pain Intensity Rating and the Daily Pain Rating Scale.…”
Section: Resultsmentioning
confidence: 99%
“…Phantom limb pain can be addressed with different psychological treatments. Early findings, mainly based on case reports, support the use of hypnosis (Grade of recommendation: D) (Rosén et al, 2001 ; Oakley et al, 2002 ; Bamford, 2006 ; Niraj and Niraj, 2014 ), biofeedback interventions (Grade of recommendation: D) (Belleggia and Birbaumer, 2001 ; Flor et al, 2001 ; Harden et al, 2005 ), Eye Movement Desensitization and Reprocessing therapy (EMDR) (Grade of recommendation: D) (Schneider et al, 2008 ; de Roos et al, 2010 ), and mirror therapy (Grade of recommendation: D) (Brodie et al, 2007 ; Chan et al, 2007 ; Murray et al, 2007 ; Mercier and Sirigu, 2009 ; Seidel et al, 2011 ) in the treatment of this condition, although there is no general agreement on the effectiveness of the latter.…”
Section: Evidences and Discussionmentioning
confidence: 99%
“…Most studies showed a significant decrease in pain intensity. Bamford (2006) reported a slight increase in pain during follow‐up after the initial decrease, but pain intensity was still significantly lower than baseline values. In addition to pain reduction, Brown and Lido (2008) reported significantly less interference in lifestyle after reflexology treatment, but no significant improvement in quality of sleep.…”
Section: Resultsmentioning
confidence: 87%